KARAKTERISTIK DOSEN IDEAL BERDASARKAN PERSEPSI CALON GURU MATEMATIKA - Ernawati, Lusia Greitha; Ruslau, Maria Fransina Veronica; Nur'aini, Khumaeroh Dwi (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2024)
This research was conducted to obtain lecturer profiles according to student perceptions. The attributes used in this research are discipline, authority, learning methods, material delivery, assignments, material review, remedial, and assessment which will then be analyzed using conjoint analysis. The conjoint analysis process with the help of SPSS 20 produces 16 attribute combinations which will then be distributed to students in the form of a questionnaire for assessment. Based on student assessments, the combination of attribute levels that has the highest preference value is lecturers who are disciplined in arriving on time, authoritative as individual lecturers, using conventional learning methods, delivering material using pure mathematics, lecturers who give assignments after being checked and then return them, carry out reviewing material before the exam, lecturers who carry out remediation, and also lecturers who provide objective assessments. The results of the conjoint analysis show that the attribute that has the highest relative importance value is reviewing the material with the attribute level that has the highest usefulness value, namely the lecturer reviewing the material before the exam. Next, successively based on the importance of the attributes, namely the attributes of discipline, tasks, remedial, authority, assessment, learning methods and delivery of material. Characteristics of lecturers in the Mathematics Education Department that students like are lecturers who, in the learning process, always review the material before taking exams; arrive on time for lectures; when giving assignments it is corrected, graded and then returned to the student; conducting re-exams for students who have not completed them or wish to improve their grades; and of course a lecturer must have authority as a lecturer; then in carrying out the assessment, the lecturer gives an assessment to the student objectively without considering the closeness of the lecturer to the student or other factors that influence the lecturer's assessment of the student; students prefer lecturers who teach without having to use techniques according to the lecturer's professionalism, the important thing is that the material presented can be understood by students; as well as delivering material using pure mathematics which can deepen students' mathematical knowledge